(untitled) (International Journal of Engineering and Computer Science, 2015)
Now a day’s people don’t have much time due to their intensive schedule. And roads have become much more crowdy to drive. So everyone wants to reach the destination as early as possible. Therefore transportation has become a major issue. To over-come such problems Radio Frequency Identification (RFid) can be used. In this paper we would see how RFid can be used for transport related problems for Indian roads. Here in collaboration with RFid we have also used Global System for Mobile Communication (GSM) and Enhanced Circuit Switched Data on GSM (ECSD) which has increased the range and scope of our project. Here we are going to see certain traffic problems and how we can over-come them using RFid.